The Need for Roads in the History of Mankind and the Emergence of Caravan Routes as the First Communication System - Lutfullaevich, Salimov Bakhriddin; Sobirjonovich, Qoraboev Murodil; Xasanovich, Xursanov Jasurbek (International Journal on Orange Technologies, 2023)
In the article, the term communication is generally used in two directions: first, in road and transport infrastructure; the second is in the field of information systems. It is analyzed that these two areas differ from each other in terms of essence and content, and the role of ancient caravan routes in the formation of human society.